A practical demonstration of electronic promotion in the reduction of ceria coated PGM catalysts - Acerbi, N; Tsang, S; Golunski, S; Collier, P (2008)
When ceria is deposited over supported PGM catalysts its reducibility is dependent on the work function of the underlying metal. © The Royal Society of Chemistry.